Oncogenic roles of the cholesterol metabolite 25-hydroxycholesterol in bladder cancer - Wang, Chen (Oncol Lett, 2020)
Oxysterols, such as 24S-hydroxycholesterol and 25-hydroxycholesterol are oxidation products of cholesterol generated by enzymatic reactions. The pathological effects of oxysterols have been described in multiple types of cancer, including cancers of the skin, lung, colon, breast and bile ducts. The molecular mechanisms underlying oxysterol-induced cancer initiation and progression have yet to be completely elucidated, and to the best of our knowledge, no prior data on the role of 24S-hydroxycholesterol and 25-hydroxycholesterol in bladder cancer exists. The results of the present study demonstrated that 25-hydroxycholesterol is increased in bladder cancer tissues, and that it promotes proliferation and the epithelial-to-mesenchymal transition in human T24 and RT4 bladder cancer cells. It was also observed that 25-hydroxycholesterol promotes Adriamycin resistance in T24 and RT4 cells, and that high levels of 25-hydroxycholesterol in bladder cancer are associated with a poor outcome. Therefore, 25-hydroxycholesterol, a primary metabolite of cholesterol, may serve an important role in the progression of bladder cancer.